Validating New Software for Semiautomated Liver Volumetry – Better than Manual Measurement? - Noschinski, L. E.; Maiwald, B.; Voigt, P.; Wiltberger, G.; Kahn, T.; Stumpp, P. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: This prospective study compared a manual program for liver volumetry with semiautomated software. The hypothesis was that the semiautomated software would be faster, more accurate and less dependent on the evaluator’s experience.Materials and Methods: Ten patients undergoing hemihepatectomy were included in this IRB approved study after written informed consent. All patients underwent a preoperative abdominal 3-phase CT scan, which was used for whole liver volumetry and volume prediction for the liver part to be resected. Two different types of software were used: 1) manual method: borders of the liver had to be defined per slice by the user; 2) semiautomated software: automatic identification of liver volume with manual assistance for definition of Couinaud segments. Measurements were done by six observers with different experience levels. Water displacement volumetry immediately after partial liver resection served as the gold standard. The resected part was examined with a CT scan after displacement volumetry.Results: Volumetry of the resected liver scan showed excellent correlation to water displacement volumetry (manual: ρ = 0.997; semiautomated software: ρ = 0.995). The difference between the predicted volume and the real volume was significantly smaller with the semiautomated software than with the manual method (33 % vs. 57 %, p = 0.002). The semiautomated software was almost four times faster for volumetry of the whole liver (manual: 6:59 ± 3:04min; semiautomated: 1:47 ± 1:11 min).Conclusion: Both methods for liver volumetry give an estimated liver volume close to the real one. The tested semiautomated software is faster, more accurate in predicting the volume of the resected liver part, gives more reproducible results and is less dependent on the user’s experience.Key points:• Both tested types of software allow exact volumetry of resected liver parts.• Preoperative prediction can be performed more accurately with the semiautomated software.• The semiautomated software is nearly four times faster than the tested manual program and less dependent on the user’s experience.Citation Format:• Noschinski L. E., Maiwald B., Voigt P. et al. Validating New Software for Semiautomated Liver Volumetry – Better than Manual Measurement?. Fortschr Röntgenstr 2015; 187: 788 – 794
Keywords: liver; CT; image manipulation/reconstruction; segmentation; surgery; tissue characterization